Abu Darda’s Model Of Moral And Spiritual Education: A Qur’anic Perspective For Contemporary Pedagogy - Supriatin, Iit; Rustandi, Redi; Alfan, Romady; Suciyati, Yati; Rohman, Dandi Abdul (PT. Student Rihlah Indonesia, 2025)
This study addresses the growing need for moral and spiritual educational models in contemporary Islamic education, especially amidst the dominance of formalistic and secular approaches. It aims to explore the Qur’anic-based educational values exemplified by Abu Darda’ raḍiyallāhu ‘anhu, a Companion of the Prophet renowned for his spiritual wisdom and contribution to Islamic learning. Employing a qualitative method with literature-based conceptual and historical analysis, this research finds that Abu Darda’s educational model is integrative—combining moral exemplarity, inner purification (tazkiyah al-nafs), and the lived application of Qur’anic values. The model emphasizes holistic character formation beyond cognitive achievement. This study contributes new insights by positioning Abu Darda’s model as a strategic alternative for Islamic educational transformation. Its implications include curriculum reform, teacher empowerment as spiritual mentors, and a shift toward value-based pedagogy in policy development.